Face Detection and Recognition Techniques through the Cloud Network: An Exploratory Study - Reddy, Manjunath; Bodepudi, Anusha; Mandapuram, Mounika; Gutlapalli, Sai Srujan (ABC Journal of Advanced Research, 2020)
Face recognition is one of the fundamental functions performed by biometrics, and it is becoming increasingly influential as new technologies like the internet and digital cameras require improved security critical features. Other applications also make use of face recognition. Face recognition software can work with static photos or visual sequences to accomplish tasks. In addition, it can handle either one of the following tasks: face identification (also known as face recognition) or face verification (also known as face authentication). People can quickly and reliably recognize known faces and identities, even when presented with challenging viewing conditions such as changing illuminations, occlusion, scale, or rotation. This ability is a hallmark of the human species. Motivated by its significance in human-to-human communication and leading to various applications, ranging from biometrics to human-computer interaction, the face recognition challenge is an essential issue in the field of computer vision as well as other related areas. Finally, this article provides a summary of the most recent and cutting-edge strategies that have been developed to deal with challenging tasks like the one being discussed.